ANALISIS IMPLEMENTASI PENGELOLAAN DANA DESA DI DESA SWASEMBADA PESISIR - Ekaputri, Retno Agustina (Convergence: The Journal of Economic Development, 2022)
The purpose of this research is to analyze on the implementation of village fund program in the coastal self sufficiency villages Pondok Kelapa District, Bengkulu Tengah Regency. The variables are studied: Accountability, Transparency and Participation perceived by the village level government, village fund management and village communities. Data collected from 97 respondents from 3 villages: Pasar Pedati, Pekik Nyaring and Pondok Kelapa. Results show that: (1). Perception of respondents against 14 indicators of transparency showed already in the very good category with an average total score of 4,32, (2). Perception 16 accountability indicators show already in the very good category with an average total score of 4,43,(3). Participation of respondents to 9 indicators show participation in good categories with an average total score of 4,19. Keywords : Village Fund Programs1, Transparency2, Accountability3, Participation 4